Effect of hCG administration on ovulation and estrus in Saanen goats subjected to short-term estrus synchronization protocol during the breeding season - Dogan, I; Toker, MB; Aktar, A; Yilmaz, MM; Udum, D (Journal of the Hellenic Veterinary Medical Society, 2023)
This study aimed to compare the effect of hCG administered at 24 or 36 h following a short-term estrus synchronization treatment on the ovulation time and estrus parameters in non-lactating Saanen goats during the breeding season. The estrous cycles of does were synchronized with an intravaginal sponge containing 60 mg of medroxyprogesterone acetate (MAP) for six days, and an injection of 125 µg of d-cloprostenol at the time of sponge insertion in addition to an injection of 300 IU of eCG 24h before sponge removal. After removal of the sponges, does were injected intramuscularly either 1 ml physiological saline (0.9% NaCl) solution after 12 h (Group1/Control; n=10), 100 IU hCG after 24 h (Group2; n=9) or 100 IU hCG after 36 h (Group3; n=9). Estrus behavior after sponge removal was observed twice daily for 84 h using teaser bucks and transrectal ovarian ultrasonography was performed twice a day for seven days to determine small, medium and large follicle numbers, luteal development and the time of ovulation. Blood samples were collected on the same days to determine serum progesterone (P4) and estradiol (E2) concentrations. No significant differences were observed in terms of estrus parameters, ovarian structure and serum P4 and E2 concentrations between the hCG-treated groups and the control group. Average values observed for all groups: estrous response (53.57%), the interval from sponge removal to estrus and ovulation (35.2 h and 67.86 h, respectively), duration of estrus (18.4 h), the interval from estrus onset to ovulation (50.37 h), ovulation rate (96.43%), number of ovulations (1.36), ovulatory follicle diameter (6.86 mm), corpus luteum diameter (8.22 mm), follicle and luteal growth rate (1.17 and 0.68 mm/day, respectively). In conclusion, administration of hCG at 24 or 36 h following a short-term estrous synchronization protocol does not affect ovulation time, estrus parameters, and serum P4 and E2 concentrations in goats during the breeding season.